Pengaruh Lingkungan, Beban Kerja Dan Konflik Kerja Terhadap Kinerja Pegawai Dinas Pekerjaan Umum Dan Tata Ruang Kabupaten Agam - Nofrita, Rafika; Ariany, Ria (CV. ITTC INDONESIA, 2024)
The Public Works and Spatial Planning Agency of Agam Regency has the main task in accordance with the Regulation of the Regent of Agam Number 51 of 2016 concerning the Position, Organizational Structure, Duties, Functions and Work Procedures of the Public Works and Spatial Planning Agency to assist the Regent in carrying out government management affairs that are the authority of the Region and assistance tasks in the Field of Public Works and Spatial Planning. This study aims to determine the Influence of the Environment, Workload and Work Conflict on the Performance of Employees of the Public Works and Spatial Planning Agency of Agam Regency. Quantitative research method. The sample in this study was all employees of the Public Works and Spatial Planning Agency of Agam Regency totaling 116 people. The results of the study showed a positive and significant influence of the environment on the performance of employees of the Public Works and Spatial Planning Agency of Agam Regency. There is a positive and significant influence of workload on the performance of employees of the Public Works and Spatial Planning Agency of Agam Regency. There is a positive and significant influence of work conflict on the performance of employees of the Public Works and Spatial Planning Agency of Agam Regency.